(untitled) (REMUNOM, 2025)
Objective: To verify the adoption of prophylactic measures for hepatic encephalopathy, hepatorenal syndrome and spontaneous bacterial peritonitis in patients with liver disease admitted due to variceal gastrointestinal bleeding to the emergency department of a public hospital. Methods: Cross-sectional descriptive study with 36 individuals treated between January 2022 and December 2024. The variables investigated included the clinical and epidemiological profile of chronic liver disease, Child Pugh and West Haven scores, imaging tests and medications (lactulose, albumin and antibiotics). Data were collected from electronic medical records, organized in Microsoft Excel 2010 for subsequent statistical analysis in SPSS 22 software. Quantitative variables were expressed as mean ± standard deviation and qualitative variables were expressed as absolute (relative) frequency. Results: There was a prevalence of male gender (66.7%), mean age of 54.4 ± 11.2 years, alcoholic etiology (77.8%) and hematemesis (61.1%). It was demonstrated most individuals were classified with low liver function reserve like: Child B (47.2%) and Child C (38.9%). Furthermore, hepatic encephalopathy was absent in the majority sample (69.4%). Among those who underwent parancethesis, 36.1% of them, none presented spontaneous bacterial peritonitis. The most adopted prophylaxis were lactulose (66.7%) and antibiotics (66.7%), with albumin (8.3%) being less frequent. Conclusion: Similarity was identified, with previous studies, a typical pattern of the clinical epidemiological profile of decompensated liver disease characterized by significant liver dysfunction. Due to adequate management of complications of variceal bleeding, there was a low incidence of hepatic encephalopathy, use of albumin to prevent hepatorenal syndrome and absence of spontaneous bacterial peritonitis.